The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1111/j.1752-1688.2003.tb04412.x
|View full text |Cite
|
Sign up to set email alerts
|

APPLICATION OF A MULTIPURPOSE UNEQUAL PROBABILITY STREAM SURVEY IN THE MID‐ATLANTIC COASTAL PLAIN1

Abstract: A stratified, spatially balanced sample with unequal probability selection was used to design a multipurpose survey of headwater streams in the Mid‐Atlantic Coastal Plain. Objectives for the survey include unbiased estimates of regional stream conditions, and adequate coverage of unusual but significant environmental settings to support empirical modeling of the factors affecting those conditions. The design and field application of the survey are discussed in light of these multiple objectives. A probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…All three distributions are similar for all subregions combined. Similar analyses for separate subregions indicated that bias among sampled streams in terms of watershed size, agricultural area, and urban area was also limited (Ator et al, 2003) Despite the rejection and replacement of a considerable number of primary streams, the desired land use distribution was maintained in the Mid-Atlantic Coastal Plain survey without sacrificing the probabilistic design (Ator et al, 2003). Site rejections during field reconnaissance may be less problematic in areas for which more accurate, regionally consistent data are available for defining the sampling frame.…”
Section: Mid-atlantic Coastal Plain Stream Study Designmentioning
confidence: 90%
See 3 more Smart Citations
“…All three distributions are similar for all subregions combined. Similar analyses for separate subregions indicated that bias among sampled streams in terms of watershed size, agricultural area, and urban area was also limited (Ator et al, 2003) Despite the rejection and replacement of a considerable number of primary streams, the desired land use distribution was maintained in the Mid-Atlantic Coastal Plain survey without sacrificing the probabilistic design (Ator et al, 2003). Site rejections during field reconnaissance may be less problematic in areas for which more accurate, regionally consistent data are available for defining the sampling frame.…”
Section: Mid-atlantic Coastal Plain Stream Study Designmentioning
confidence: 90%
“…A stratified random sample with unequal probability selection (within each stratum) was used to select individual streams for sampling (Ator et al, 2003). The survey was designed to include 175 streams, including 25 within each subregion.…”
Section: Mid-atlantic Coastal Plain Stream Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary purpose of this design was to provide data needed to develop good empirical models (Ator et al 2003). Two problems that often plague modeling efforts can be addressed at the sample selection stage are too little variability among important predictors and multicollinearity among predictors.…”
Section: Watershed Sampling Designmentioning
confidence: 99%